2013
DOI: 10.1016/j.juro.2013.03.078
|View full text |Cite
|
Sign up to set email alerts
|

High Diagnostic Ability of Multiparametric Magnetic Resonance Imaging to Detect Anterior Prostate Cancer Missed by Transrectal 12-Core Biopsy

Abstract: Prebiopsy multiparametric magnetic resonance imaging has the potential to efficiently select men who could advantageously undergo anterior samplings, in addition to transrectal 12-core prostate biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 25 publications
0
44
0
1
Order By: Relevance
“…A total of 8663 original studies in English were identified and 15 were analyzed. [2][3][4][6][7][8][23][24][25][26][27][28][29][30][31] The overall quality varied from low to moderate. Fourteen conference abstracts will require followup in future updated versions.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 8663 original studies in English were identified and 15 were analyzed. [2][3][4][6][7][8][23][24][25][26][27][28][29][30][31] The overall quality varied from low to moderate. Fourteen conference abstracts will require followup in future updated versions.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…• In two studies 23,25 with a prevalence of CSPC of 21-30%, the ranges of sensitivity, specificity, positive predictive value, and negative predictive value of mpPMRI to detect CSPC were 68-94%, 21-72%, 24-50%, and 83-94%, respectively.…”
Section: Key Evidencementioning
confidence: 98%
See 1 more Smart Citation
“…Recently, Al-Ahmadie et al [14] in 1,312 radical prostatectomies demonstrated that 197 (15%) PCa were located in the AZ of the gland and characterized by a superimposable grading and staging in comparison with PZ PCa; Iremashvili et al [22] reported a higher rate of positive surgical margin in the presence of TZ cancer in comparison with PZ PCa in 1,141 men submitted to radical prostatectomy. In the last years, magnetic resonance imaging and magnetic resonance imaging/ultrasound fusion-guided biopsy have increased the detection of PCa at repeat biopsy, with an estimated incidence equal to 30-50% of cases [5,6,7]; in this respect, transperineal prostate biopsy demonstrated a better accuracy in comparison with the transrectal approach in the diagnosis of AZ cancers [23]. On the other hand, still today the incidence and clinical relevance of AZ cancers diagnosed in case of initial prostate biopsy are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 15 studies, one was an RCT [55], five were prospective studies [2,56,57,60,65], six were retrospective studies [3,59,61e64] and three did not report their study designs [54,58,66] (Table 1).…”
Section: Study Design and Qualitymentioning
confidence: 99%